The Improvement of the Student`s Learning Achievement in Natural Scince by using Inquiry Models in Elementary School - Harjulita, Harjulita; Zuryanty, Zuryanty; Silvinia, Silvinia (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
AbstrackThis research was conducted due to the fourth grade student`s low learning achievement at SD Negeri 14 Gadut Kecamatan Tilatang Kamang. The aim of this research was to describe the improvement of the student`s learning achievement in Natural Scince by using inquiry model in the fourth grade of SD 14 Gadut Kecamatan Tilatang Kamang. This was a classroom action research  which applied qualitative and quantitative approaches. The result of the research indicated that the student`s learning achievement improved from 75,94% in the first cycle into 87,78%  in the second cycle . Hence, the use of inquiry model could improve the student’s learning achievement in Natural Science in the fourth grade of SD 14 Gadut Kecamatan Tilatang Kamang.keyword : Learning Outcomes, Science Studies, Inquiry Model